VLADIMIR VERNADSKY: SOCIAL, CULTURAL, HISTORY MEASUREMENT OF SCIENCE - Shashkova, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The author conceptualized the ideas of Vernadsky social history of science, the problems of relationship between science, philosophy and religion in the cultural and historical context.